1983
DOI: 10.1128/jcm.18.3.550-553.1983
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection and identification of herpes simplex virus in cell culture by a direct immunoperoxidase staining procedure

Abstract: Cell monolayers were inoculated with 169 fresh and 76 previously frozen clinical specimens and examined for the presence of herpes simplex virus (HSV) by noting the appearance of characteristic cytopathic effect (CPE) and by using a direct immunoperoxidase (IP) stain for viral antigen. HSV was detected by IP staining in 40 of 169 (23.7%) monolayers and by CPE in 39 of 169 (23.1%) monolayers inoculated with fresh specimens. All 40 isolates were detected and confirmed by IP staining within 24 h. Although 39 of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
2
23
1
Order By: Relevance
“…Only 26% of the positive specimens could be detected at 24 h by the TC-CPE method. The average time required for detection of an IHSV-positive specimen by the TC-CPE method was 2.4 days, which was comparable to that in another published report (7). By combining viral culture with the sensitive biotin-avidin fluorescence technique, we have found that HSV can be rapidly and accurately detected in clinical samples.…”
Section: Methodssupporting
confidence: 79%
“…Only 26% of the positive specimens could be detected at 24 h by the TC-CPE method. The average time required for detection of an IHSV-positive specimen by the TC-CPE method was 2.4 days, which was comparable to that in another published report (7). By combining viral culture with the sensitive biotin-avidin fluorescence technique, we have found that HSV can be rapidly and accurately detected in clinical samples.…”
Section: Methodssupporting
confidence: 79%
“…The RAMP Clinical specimens were obtained from throats (n = 165), other oral sites (n = 50), genital lesions (n = 35), skin lesions (n = 19), and tissue sites (n = 4) of bone marrow transplant 8 Corresponding author. patients (prior to transplantation, al patients were screened for HSV immune status).…”
mentioning
confidence: 99%
“…However the problem may well lie in the kits' use of Vero cells which are fairly insensitive to HSV infection when compared with more widely used HDF or primary RK cells. When other workers used HDF cell culture followed by IP staining at 24 hr, all HSV isolates were detected at 24 hr by IP staining that were eventually detected by standard culture (Miller and Howell, 1983). An additional study demonstrated that it is possible to significantly shorten the time involved in maintaining and observing cell cultures by application of the PAP technique for early detection of HSV in HDF cell culture.…”
Section: Immunoperoxidasementioning
confidence: 99%